Filsafat Tarbiyah Berbasis Kecerdasan Makrifat - Mulkhan, Abdul Munir (Jurnal Pendidikan Islam, 2013)
Philosophy is the source of science and technology. The practice of Islamic Education works without being guided by Tarbiyah (Islamic Education) Philosophy, but by the seculer thinking, It develops without orientation and it is hard to compete with others. It’s time the Islamic education pratice to guiding by the Tarbiyah Philosophy, Tarbiyah Theories and Tarbiyah Technology which is structurally and functionally built from Islamic philosophy. As of the basic idea of Islamic philosophy, the essential of Tarbiyah Philosophy is Ma’rifat Quotients wich means the activity for understand and realize the presence of God in whole life, activities of man; that also means the knowledge about God and intimate relationship with Him. The practical of Tarbiyah Philosophy based on Ma’rifat Quotients it both a creative solution for all kind of education problems and alternatif educational model. Based on Ma’rifat Quotients, it can be used to develop boarding school in more effcient way to accelerate qualities learning only 8 years for elementary to senior high school before join to university.